Veterinarians as first responders in disaster management: Integrating animal health and welfare into disaster management frameworks - Levak, Jelena; Radin, Lada (Crisis Management Days, 2025)
Introduction Natural disasters have severe and far-reaching impacts on human and animal health, economic stability, and ecosystems. Animals—livestock, companion animals, and wildlife—are critical components of societal resilience in times of crisis. An animal in a disaster can be a victim, a danger, a source of food, a rescuer or a sentinel. Under the One Health framework, human, animal, and environmental health interdependence is well recognized. However, despite this awareness and approach, advocated mainly by veterinary groups, many European countries lack appropriate frameworks to address animal health and welfare during disasters. The World Organisation for Animal Health (WOAH, formerly the Office International des Epizooties (OIE)) has emphasized integrating animal health and welfare into disaster preparedness and response strategies. A 2023 survey of WOAH European members reveals that: Only 51% of countries include animal welfare in their disaster risk frameworks. 39% report limited or no legal authority to manage animal-related emergencies. Veterinary services are involved in disaster management but often face coordination and resource challenges (WOAH, 2023). This paper proposes a strategic approach to position veterinarians as first responders in disaster scenarios, advocating for policy reform, training programs, and the development of standard operating procedures (SOPs). Methodology This qualitative study synthesizes data from WOAH’s 2023 regional survey, organizational guidelines, and literature on disaster management through One Health approach. A thematic analysis identified patterns in legal authority, coordination mechanisms, and preparedness across European countries. The research also reviewed WOAH simulation exercises and existing case studies where veterinarians participated in disaster response. The goal was to assess current limitations and outline actionable pathways for integrating veterinary services into emergency systems. Main Results The analysis identified several core challenges that currently prevent the effective integration of veterinarians into disaster management systems across Europe. First, there is limited policy integration of animal welfare in disaster risk frameworks. Many European countries still do not formally recognize animal health and welfare as a component of national disaster preparedness and response. As a result, emergencies involving animals are often inadequately addressed, despite their clear impact on public health and metal health, environmental sustainability and economic recovery. Second, veterinary services frequently lack the necessary training and resources to respond effectively to disasters. Most countries do not provide veterinarians with specialized education or operational protocols for managing crises such as evacuations, sheltering, triage, or zoonotic disease prevention. This results in an underutilization of veterinary expertise at times when it is critically needed. Third, collaboration between veterinary authorities and civil protection systems remains inconsistent and fragmented. In many cases, there are no clearly defined roles for veterinary services within national emergency frameworks. This lack of coordination leads to confusion, inefficiencies, and delays in response efforts during disasters. Fourth, the impact of disasters on animals—particularly livestock and companion animals—has significant secondary effects on human communities. Large-scale events such as floods and wildfires have caused mass displacement and mortality among animals, leading to financial losses, disrupted livelihoods, and increased risk of disease transmission. The absence of veterinary involvement in managing these situations exacerbates the consequences for affected populations. Despite these challenges, the study identified several key opportunities to strengthen disaster resilience through the active involvement of veterinarians as first responders. Their medical training, understanding of animal health and welfare, and trusted role in communities make them well-suited to contribute across multiple phases of disaster management. They can lead or support evacuation processes, provide emergency veterinary care in shelters, monitor and contain zoonotic disease outbreaks, and help restore livestock-based economies in rural areas.